Safety and efficacy of amiodarone in arrhythmias – a prospective study in the South Indian population - Janardhan, Vasantha; K, Kousalya; S, Ramalakshmi; Rani N, Vanitha; G, Kannan; G, Jyothsna; M R C, Uma (Indian Journal of Pharmacy Practice)
To study the cardiac and non-cardiac safety of amiodarone and measure the efficacy of amiodarone in restoring and maintaining sinus rhythm. 35 patients on amiodarone therapy were examined for its safety and efficacy during a period of 6-months. The dosing schedule of amiodarone in the study population was as follows: I.V. loading doses of 150-300 mg bolus over 30 minutes, followed by 1 mg per minute for 6 hours, followed by daily oral maintenance dose of 100-400 mg; I.V. + oral loading dose of 800-2320 mg per day, to a total dose of up to 10 gm, followed by daily oral maintenance dose of 100-400 mg; Oral loading dose of 200 mg T.D.S. for 5 days followed by 200 mg B.D. for 5 days and a daily oral maintenance dose of 100-200 mg O.D. Out of 35 patients, only 2 patients developed severe ADR (hypothyroidism) and discontinued amiodarone therapy. Amiodarone could restore rhythm in 15 (83.33%) out of 18 patients with Ventricular Tachyarrhythmias (VT) and in 10 (83.33%) patients out of 12 patients with Atrial Fibrillation (AF). In other types of arrhythmias (Supraventricular Tachycardia (SVT), Ventricular Tachycardia (VT), Ventricular Premature Complexes (VPCs) & Supraventricular Premature Complexes (SVPCs), amiodarone could restore rhythm in 5 (100%) out of 5 patients. Amiodarone was found to be safe and effective in treating all types of arrhythmias.
Keywords: amiodarone; arrhythmias; efficacy